Two new taxa of marcgraviastrum (marcgraviaceae) and a catalogue of colombian taxa of this genus1 (2012)
A new species of Marcgraviastrum is validated, described, and illustrated. The new species is known only from the Colombian Guayana (Departments of Caquetá, Guaviare, and Vaupés). Its morphological relationships are discussed. Furthermore, a new combination into Marcgraviastrum is published. A checklist of the nine Colombian species of the genus is presented.